Increased Arbekacin Clearance in Patients With Febrile Neutropenia. Issue 1 (February 2020) - Nakayama, Takahiro; Chuma, Masayuki; Tochikura, Naohiro; Iwabuchi, So; Suzuki, Shinichiro; Matsumoto, Chiaki; Imai, Toru; Hamada, Takashi; Nakagawa, Masaru; Takahashi, Hiromichi; Uchino, Yoshihito; Miura, Katsuhiro; et al.
Abstract : Background: Arbekacin (ABK) is used to treat infections caused by methicillin-resistant Staphylococcus aureus and is used widely for the treatment of febrile neutropenia (FN). As ABK has a narrow therapeutic concentration window, the dosage must be adjusted via therapeutic drug monitoring. However, the influence of the physiology of patients with FN on the pharmacokinetic (PK) parameters of ABK remains unclear. Therefore, we examined this influence on ABK PK parameters. Method: We performed a retrospective cohort study using data from patients with a hematologic malignancy who were ≥18 years and had been administered ABK. We excluded patients who did not receive therapeutic drug monitoring and had an estimated glomerular filtration rate (eGFR) of <30 mL/min, because clinically sufficient data would not be available. Result: Of the 99 enrolled patients, 25 did not have FN and 74 had FN. Arbekacin clearance (CLabk) was shown to correlate with eGFR in patients with FN (r = 0.32, P = 0.0062) and without FN (r = 0.50, P = 0.01). CLabk was higher in patients with FN than in those without FN. In addition, in the eGFR of <100 mL/min group (normal renal function), CLabk and CLabk/eGFR were also higher in patients with FN than in those without FN. Conclusions: CLabk was increased in patients with FN and normal renal function; therefore, we propose an increased ABK dose for patients with FN and normal renal function.